The Effectiveness of Mind Mapping Phonetic Symbol Media to Eliminate The Confusion of Pronunciation: The Effectiveness of Mind Mapping Phonetic Symbol Media to Eliminate The Confusion of Pronunciation - M. Hilmy Hidayatullah; Annisa Kurniaasri; Ismil Asiffin; Sirrul Bari (JOEY: Journal of English Ibrahimy, 2022)
Pronunciation was one of difficult skill, it made many people confused. This research aimed to determine a solution by using mind mapping phonetic symbol media to eliminate the confusion of pronunciation. The content of mind mapping showed the part of phonetic symbol to study the sound of words. It has helped the understanding of some difference sounds. This research used quantitative true-experimental method by pre-posttest control group design. The tests carried out are validity, reliability, descriptive analysis, and t-test. Subject of this research is 30, it was divided 15 students for experiment group and 15 control group. The sample was taken by using random sampling and applied Slovin formula. While, the data was obtained by using reading test. The value of descriptive analysis there was a raising value which can be seen from mean post-test experiment group 72 it was higher than control group 36.6. And also, the quarrel of normal gain between experiment group and control group showed 75%>28.57%, 3 students from experiment group than a student of control group. Furthermore, the value of t-test was there was an influence to eliminate the confusion of pronunciation by using mind mapping phonetic symbol, it can be seen from the trials that have been tested in SPSS obtaining a t-count value of 8,290 > 1,7, it can be said that H0 is rejected and Ha accepted which it means that There is an influence of mind mapping phonetic symbol media (X) to eliminate the confusion of pronunciation (Y).